Review of the marine isopod crustacean genus Hansenium Serov and Wilson, 1995 (Asellota: Stenetriidae) from tropical Australia and Papua New Guinea, with description of a new genus - Bruce, Niel L.; Buxton, Chad (Zootaxa, 2013)
The genus Hansenium is revised and a new diagnosis presented. A neotype is designated for the type species Hansenium hanseni (Müller, 1991), and the genus is restricted to the type species and Hansenium remocarpus Kensley and Schotte, 2002. Machatrium gen. nov. and the following species are described: Machatrium falcensis sp. nov. (type species), Machatrium thungku sp. nov. from Lizard Island, Great Barrier Reef; Machatrium wongat sp. nov. from Madang, Papua New Guinea, Machatrium tropex (Bolstad and Kensley, 1999), comb. nov. also from Madang, Papua New Guinea; a fur-ther five species are transferred from Hansenium to Machatrium gen. nov. The remaining species of Hansenium are re-tained as incertae sedis in their existing combination (11 species), reallocated to other genera (1 species) or regarded as species inquirenda (3 species). The principal differentiating characters of Hansenium, Machatrium gen. nov. and Stene-trium Haswell, 1881, are the pseudorostrum being short and trapezoid or long and anteriorly narrowed, morphology of the male pereopod 1, notably the shape of the propodus inferior margin, presence or absence of a process on the inferodistal margin of the merus and carpus; and the apex of the appendix masculina being acute or blunt, with or without a concavity and with or without terminal setae.